Changes in the narrative structure of Netflix series: The mindhunter case (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2020)
This paper examines the impact of Netflix simultaneous release on the narrative structure of Mindhunter (2017- Today). The analysis of its first season shows that it adopts a structural model unconstrained by the procedural format formula, and that the season is conceived as a feature film that develops a complex main character. Simultaneous release impacts in cliffhangers and episodic plots too, as they become less prominent.
Keywords: Structure; narrative; Netflix; series; Mindhunter